Non-paraxial Talbot effect in one-dimensional gratings with period comparable to the wavelength - Arrieta, E. (2017)
The Talbot effect is a diffractive phenomenon which was found since its inception in the Gaussian optics, but when the period of the object is comparable with the wavelength is considered entering its non-paraxial regime. There, it has attracted interest for its applications related to the design of objects and their restorative effects posing in damaged gratings on this scale. In this contribution a study of this phenomenon at level non-paraxial (metaxial) is presented by using scalar diffraction theory in plane waves representation for periodic transversal fields. To this end, a one-dimensional amplitude grating of period p is used which is illuminated by a monochromatic plane wave of wavelength λ where p ranges between 1,5 λ and 4,2 λ.